(untitled) (Journal of Educational Sciences, 2024)
The training of future teachers of natural sciences who can teach specialized subjects in English requires new approaches to teaching a foreign language and the development of certain competencies from higher educational institutions of the Kazakhstan Republic. The purpose of this work is to create a productive rubric for evaluating foreign language communicative competence (FCC) at three levels of its development: satisfactory, optimal, and sufficient. The theoretical significance of the study contributes to the use of a descriptive heading with criteria when disclosing the main components of the FCC. The significance of the conducted research in practice consists of the proposal to use a new heading for students of non-linguistic specialties, which will increase the effectiveness of the development of the FCC and its components. The task of the study was to specify each component of foreign language communicative competence and to develop a rubric as a formative assessment tool. The solution of the tasks was based on general scientific methods within the framework of comparative and logical analysis, as well as the analysis and interpretation of knowledge in the field of foreign language education. A feature of the creation of the rubric was an adequate assessment of the level of FCC, consideration of pan-European requirements, and a new form of FCC control. The result of the work done can help teachers and students of pedagogical specialties to start or continue to work on the development of FCC based on determining the current level of its proficiency. Key words: criteria assessment, rubrics, foreign language communicative competence, foreign language.